The Voice of Gifted Students on Triggered and Maintained Engagement with Learning at School - Snikkers-Mommer, Saskia; Minnaert, Alexander; Mayo, Aziza (Advances in Social Sciences Research Journal, 2025)
Although gifted students might exhibit strong task involvement, their engagement in learning at school is not a given. In this qualitative study, three in-depth case studies were used to explore what, according to the gifted students’ voices, is needed to become and to remain engaged in learning at school. The interview data were analyzed inductively and deductively with an eye toward general patterns and differences that became evident in students’ experiences. The results showed that it is essential for gifted students to be seen to become engaged. Students unfold that the fulfilment of the basic psychological needs and, in particular, the experience of an autonomy-supportive environment is crucial. Moreover, they tell us that both the educational context and themselves can be facilitating or hindering factors. To remain engaged when faced with challenges, gifted students need to feel competent, which requires structure tailored to their needs. Implications for educational practice are discussed.